Recruitment of miR-8080 by luteolin inhibits androgen receptor splice variant 7 expression in castration-resistant prostate cancer. (5th December 2019) - Naiki-Ito, Aya; Naiki, Taku; Kato, Hiroyuki; Iida, Keitaro; Etani, Toshiki; Nagayasu, Yuko; Suzuki, Shugo; Yamashita, Yoriko; Inaguma, Shingo; Onishi, Masaya; Tanaka, Yasuhito; Yasui, Takahiro; et al.
Abstract: A need exists for seeking effective treatments for castration-resistant prostate cancer (CRPC) in response to its emergence following androgen deprivation therapy as a major clinical problem. In the present study, we investigated the chemopreventive and chemotherapeutic potential of luteolin, a flavonoid with antioxidative properties, on prostate cancer, including CRPC. Luteolin inhibited the progression of rat prostate carcinogenesis by induction of apoptosis in a transgenic rat for adenocarcinoma of prostate (TRAP) model. Luteolin decreased cell proliferation in a dose-dependent manner and induced apoptosis with the activation of caspases 3 and 7 in both rat (PCai1, established from a TRAP prostate tumor) and human (22Rv1) CRPC cells. Dietary luteolin also suppressed tumor growth via an increase in apoptosis and inhibition of angiogenesis in PCai1 and 22Rv1 xenografts implanted in castrated nude mice. We also focused on androgen receptor splice variant 7 (AR-V7), which contributes to cell proliferation and therapeutic resistance in CRPC. Luteolin dramatically suppressed AR-V7 protein expression in 22Rv1 cells in vitro and ex vivo . Microarray analysis identified MiR-8080, which contains a possible target sequence for AR-V7 3′-UTR, as a gene upregulated by luteolin. MiR-8080 transfection decreased the AR-V7 expression level and the induction of apoptosis in 22Rv1 cells. Furthermore, miR-8080 knockdown canceled luteolin decreasing AR-V7 and the cell growth of 22Rv1. MiR-8080 induced by luteolin intake enhanced the therapeutic effect of enzalutamide on 22Rv1 xenografts under castration conditions. These results indicate luteolin inhibits CRPC by AR-V7 suppression through miR-8080, highlighting luteolin and miR-8080 as promising therapeutic agents for this disease. Abstract : AR-V7 has been highlighted as a major therapeutic resistance mechanism in castration-resistant prostate cancer (CRPC). This study describes a novel mechanism for downregulation of AR-V7 by miR-8080, which induces apoptosis and improves the therapeutic efficacy in CRPC.